The urgency of victim witness testimony as valid evidence from persons with disabilities is associated with Law Number 12 of 2022 concerning the Crime of Sexual Violence - Debora Sinaga; Elis Rusmiati; Agus Takariawan (Jurnal Indonesia Sosial Teknologi, 2024)
Persons with disabilities often receive discriminatory treatment, due to their physical and/or mental limitations. The Criminal Procedure Code regulates that people with disabilities can give statements without being under oath and these provisions have reduced the rights of persons with disabilities to obtain their justice rights. The Sexual Violence Crime Law regulates where the statements of witnesses and/or victims of people with disabilities can be under oath. The approach method used in this research is a normative juridical approach that is based on formal regulations, as well as secondary data obtained from library materials in the form of scientific writings and other written sources. This research will illustrate the importance and the implication of the testimony of witnesses and/or victims with disabilities having the same legal force as the statements of witnesses and/or victims without disabilities where the testimony must be followed by the implementation of a personal assessment.